Cartilage immunoprivilege depends on donor source and lesion location. (1st September 2015) - Arzi, B.; DuRaine, G.D.; Lee, C.A.; Huey, D.J.; Borjesson, D.L.; Murphy, B.G.; Hu, J.C.Y.; Baumgarth, N.; Athanasiou, K.A.
Graphical abstract: Abstract: The ability to repair damaged cartilage is a major goal of musculoskeletal tissue engineering. Allogeneic (same species, different individual) or xenogeneic (different species) sources can provide an attractive source of chondrocytes for cartilage tissue engineering, since autologous (same individual) cells are scarce. Immune rejection of non-autologous hyaline articular cartilage has seldom been considered due to the popular notion of "cartilage immunoprivilege". The objective of this study was to determine the suitability of allogeneic and xenogeneic engineered neocartilage tissue for cartilage repair. To address this, scaffold-free tissue engineered articular cartilage of syngeneic (same genetic background), allogeneic, and xenogeneic origin were implanted into two different locations of the rabbit knee ( n = 3 per group/location). Xenogeneic engineered cartilage and control xenogeneic chondral explants provoked profound innate inflammatory and adaptive cellular responses, regardless of transplant location. Cytological quantification of immune cells showed that, while allogeneic neocartilage elicited an immune response in the patella, negligible responses were observed when implanted into the trochlea; instead the responses were comparable to microfracture-treated empty defect controls. Allogeneic neocartilage survived within the trochlea implant site and demonstrated graft integration into the underlying bone. In conclusion, the knee joint cartilage does not represent an immune privileged site, strongly rejecting xenogeneic but not allogeneic chondrocytes in a location-dependent fashion. This difference in location-dependent survival of allogeneic tissue may be associated with proximity to the synovium. Statement of Significance: Through a series of in vivo studies this research demonstrates that articular cartilage is not fully immunoprivileged. In addition, we now show that anatomical location of the defect, even within the same joint compartment, strongly influences the degree of the resultant immune response. This is one of the first investigations to show that (1) immune tolerance to allogeneic tissue engineered cartilage and (2) subsequent implant survival are dependent on the implant location and proximity to the synovium.